AVEC 2016 – Depression, mood, and emotion recognition workshop and challenge - Valstar, Michel F.; Gratch, Jonathan; Schuller, Björn; Ringeval, Fabien; Lalanne, Denis; Torres, Mercedes Torres; Scherer, Stefan; Stratou, Giota; Cowie, Roddy; Pantic, Maja (2016)
The Audio/Visual Emotion Challenge and Workshop (AVEC 2016) "Depression, Mood and Emotion" will be the sixth competition event aimed at comparison of multimedia processing and machine learning methods for automatic audio, visual and physiological depression and emotion analysis, with all participants competing under strictly the same conditions. The goal of the Challenge is to provide a common benchmark test set for multi-modal information processing and to bring together the depression and emotion recognition communities, as well as the audio, video and physiological processing communities, to compare the relative merits of the various approaches to depression and emotion recognition under well-defined and strictly comparable conditions and establish to what extent fusion of the approaches is possible and beneficial. This paper presents the challenge guidelines, the common data used, and the performance of the baseline system on the two tasks.